Growth Hormone Receptor Gene Expression in Puberty - Pagani, S.; Meazza, C.; Gertosio, C.; Bozzola, E.; Bozzola, M. (Hormone and Metabolic Research, 2015)
The mechanisms regulating the synergic effect of growth hormone and other hormones during pubertal spurt are not completely clarified. We enrolled 64 females of Caucasian origin and normal height including 22 prepubertal girls, 26 pubertal girls, and 16 adults to evaluate the role of Growth Hormone/Insulin-like growth factor-I axis (GH/IGF-I) during the pubertal period. In these subjects both serum IGF-I and growth hormone binding protein levels, as well as quantitative growth hormone receptor (GHR) gene expression were evaluated in peripheral lymphocytes of all individuals by real-time PCR. Our results showed significantly lower IGF-I levels in women (148±10 ng/ml) and prepubertal girls (166.34±18.85 ng/ml) compared to pubertal girls (441.95±29.42 ng/ml; p<0.0001). Serum GHBP levels were significantly higher in prepubertal (127.02±20.76 ng/ml) compared to pubertal girls (16.63±2.97 ng/ml; p=0.0001) and adult women (19.95±6.65 ng/ml; p=0.0003). We also found higher GHR gene expression levels in pubertal girls [174.73±80.22 ag (growth hormone receptor)/5×105 ag (glyceraldehyde 3-phosphate dehydrogenase)] compared with other groups of subjects [women: 42.52±7.66 ag (growth hormone receptor)/5×105 ag (glyceraldehyde 3-phosphate dehydrogenase); prepubertal girls: 58.45±0.18.12 ag (growth hormone receptor)/5×105 ag (glyceraldehyde 3-phosphate dehydrogenase)], but the difference did not reach statistical significance. These results suggest that sexual hormones could positively influence GHR action, during the pubertal period, in a dual mode, that is, increasing GHR mRNA production and reducing GHR cleavage leading to GHBP variations.
Keywords: IGF-I; pubertal spurt; prepubertal girls